Acute Digestive Symptoms and Lactose Malabsorption to Cow Milk or Sheep Milk in Female Dairy Avoiders. (29th May 2020) - Shrestha, Aahana; Samuelsson, Linda; Sharma, Pankaja; Cameron-Smith, David; Day, Li; Milan, Amber
Abstract: Objectives: Sheep milk (SM) is compositionally different from cow milk (CM), but maintains the nutritional benefits of CM, making it a potential alternative for CM avoiders. While dairy avoidance is often due to intolerance to lactose, which is also found in SM, there are consumer anecdotal reports that SM is better tolerated than CM. Thus, this clinical trial was undertaken to assess acute digestive comfort and lactose malabsorption comparing SM and CM in female dairy avoiders. Methods: In a double-blinded, randomized cross over trial, 30 dairy avoiding females (aged 20–30 years) drank 650 mL of SM or CM (reconstituted from spray dried powder) following an overnight fast, on separate occasions at least one week apart. Blood samples were collected for single nucleotide polymorphisms of the LCT gene (lactase gene; C/T13910 and G/A22018 ). Breath H2 and visual analog scale (VAS) digestive symptom scores were recorded at fasting and regular intervals over 4 h after ingestion. Results: Genotyping showed 80% of the dairy avoiders were lactase non-persistent (CC13910 and GG22018 genotype), hence lactose malabsorbers. Digestive symptoms were similar in response to SM and CM, with increased symptoms; abdominal cramps, rumbling, bloating, belching, flatulence, and nausea, after the ingestion of either milk ( P < 0.05). Breath H2 was greater after CM (75 ± 10 ppm), than SM (52 ± 8 ppm at 180 min; P  = 0.013) which may be due to greater lactose content in reconstituted CM than SM (30.6 vs 23.0 g). Conclusions: The differing composition of SM did not alter adverse digestive symptoms after a single portion relative to CM, although the lower lactose content reduced breath H2 response in SM. However, tolerance to SM should be further investigated with lactose matched milk (as occurs naturally) and in non-lactose related dairy intolerance to elucidate if these individuals could benefit from SM. Funding Sources: This study was funded by AgResearch PreSeed Fund, AgResearch Strategic Science Investment Fund, Blue River Dairy, and Spring Sheep Milk Company.